The impact of protective measures against COVID-19 on the wellbeing of residents in nursing homes and their relatives: a rapid review - P. Schneider; M. Abt; C. Cohen; N. Marmier; C. Ortoleva Bucher (BMC Geriatrics, 2023)
Abstract During the COVID-19 pandemic and compared to other population groups, older people were at a heightened risk of developing lethal disease symptoms. Thus, many countries put in place protective measures to protect this “at-risk” population, especially in nursing homes, to limit the number of infections. These measures consisted mostly in the absence of social gatherings, the impossibility for relatives to enter the nursing homes, limitations in group activities, and the ban of group-eating. Although these measures were helpful to mitigate the spread of the disease, they also induced long periods of social isolation for the residents of nursing homes. This could have impacted the wellbeing and quality of life of residents and their relatives, with a possible impact on the overall health of residents. We designed this rapid review to investigate the literature on the impact of COVID-19 protective measures in nursing homes on the quality of life, wellbeing and physical health of residents and their relatives. Our results showed that most of the articles included in the review, either using qualitative or quantitative methods, evidenced a detrimental impact of protective measures on resident’s and their relatives’ wellbeing. We argue that, in the event of a new pandemic similar to the COVID-19, protective measures should also take into account their psychological impact, and not only their physical impact.